8x-6+14x+8=90

Simple and best practice solution for 8x-6+14x+8=90 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x-6+14x+8=90 equation:


Simplifying
8x + -6 + 14x + 8 = 90

Reorder the terms:
-6 + 8 + 8x + 14x = 90

Combine like terms: -6 + 8 = 2
2 + 8x + 14x = 90

Combine like terms: 8x + 14x = 22x
2 + 22x = 90

Solving
2 + 22x = 90

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 22x = 90 + -2

Combine like terms: 2 + -2 = 0
0 + 22x = 90 + -2
22x = 90 + -2

Combine like terms: 90 + -2 = 88
22x = 88

Divide each side by '22'.
x = 4

Simplifying
x = 4

See similar equations:

| 7x-(7/2)(x-5)=35 | | 4(2x-3)/5=16 | | 8(x+7)-5(x+7)=3x+21 | | 3x^2+7y=18 | | m-4-2m= | | 602=45+1x | | y+b=15 | | -7(x-3)+3=2x-9(x-4) | | (7t-2)/(11t+2)=0 | | 1.95=ln(3k+1) | | 7a+13-9a=8a-3a-8 | | 3x^2-17-6=0 | | 29-x=x^2+1 | | 40=5/8v | | (7x^4-6x^3y+3xy^2-y)-(-9x^4-5x^3y-xy^2+2y)= | | 7+1x=6-3(1x-2) | | 45+x=0 | | x^2-8x=x(7+x) | | -2(x+2)=-6x(-6x-2) | | x^2+6x+18=43/2 | | 5.63-4.18x-1.1x=25.694 | | x/(x+2)(x-3)-2/(x-2)(x-3) | | 4b+1=6b-3 | | .85x=219.3 | | 1/10(a-1)=2/5(a+2)-1/5a | | 4/-4/3 | | (2x+15)+11=x+20 | | 4/5x-6=14 | | 6-6x-4x=16 | | 3(x+7)=8x+4-5x+17 | | 8y-(12y-3)=9 | | 4x-95=0 |

Equations solver categories